The Relationship Between Rehabilitation Compliance and The Quality of Life of Stroke Patients - Musrifah, Musrifah; Stiexs, Anggie; Maryuni, Sri (Global Indonesia Health Care (GOICARE), 2025)
Background: Stroke is a leading cause of long-term disability worldwide, significantly impacting patients' quality of life. Post-stroke rehabilitation is critical for restoring functional ability and independence. However, rehabilitation adherence remains a challenge, especially in low-resource settings. Purpose: This study aimed to analyze the relationship between rehabilitation compliance and the quality of life among stroke patients at Advent Hospital Bandar Lampung. Methods: A cross-sectional quantitative design was employed with purposive sampling. A total of 52 stroke patients undergoing rehabilitation were assessed using a rehabilitation compliance questionnaire and WHOQOL-BREF. Data were analyzed using a non-parametric Gamma correlation test. Results: The majority of respondents showed moderate rehabilitation compliance (47.2%) and a fairly good quality of life (69.8%). A statistically significant relationship was found between rehabilitation compliance and quality of life (p = 0.004). Patients with higher adherence demonstrated better quality of life outcomes, indicating that consistent engagement in rehabilitation is associated with improved post-stroke recovery. Conclusion: Rehabilitation compliance is significantly associated with stroke patients’ quality of life. Hospitals are encouraged to develop interventions that enhance patient motivation, education, and support systems to improve adherence and recovery outcomes.